Application of yttrium salt suspension containing dodecylbenzene sulfonic acid, yttrium oxide mesocrystal and preparation method and application of yttrium oxide mesocrystal

Through the combination of dodecylbenzenesulfonic acid and deionized water, yttrium oxide mesogen with uniform particle size distribution was prepared, which solved the problem of inconsistent powder flight speed in plasma spraying process, and improved the coating quality and wear resistance. Simplified the preparation process.

CN119191328APending Publication Date: 2024-12-27SHANGHAI UNIV OF ENG SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411121938.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-15
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

In the plasma spraying process, the uneven particle size distribution of yttrium oxide powder leads to inconsistent powder flight speed, affecting the coating quality. In addition, the existing hydrothermal synthesis preparation methods have problems such as difficult control of atomization process and uneven particle size distribution.

Method used

By using dodecylbenzenesulfonic acid as a surfactant and deionized water, the pH value and reaction conditions of the yttrium oxide suspension are adjusted, and yttrium oxide mesomorphs with low particle size distribution coefficient are prepared, avoiding atomization The particle link achieves the consistency of the flight speed of powder particles in the plasma spraying process.

Benefits of technology

Controllable synthesis of yttrium oxide mesogen is achieved, with uniform particle size distribution, improving the quality and wear resistance and corrosion resistance of plasma spray coating, simplifying the preparation process, and reducing the situation of inconsistent powder flight speed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191328A_ABST
    Figure CN119191328A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of yttrium oxide preparation, and particularly discloses application of yttrium salt suspension containing dodecylbenzene sulfonic acid, yttrium oxide mesocrystal as well as a preparation method and application of the yttrium oxide mesocrystal, and the preparation method comprises the following steps: S1, carrying out hydrothermal reaction on the yttrium salt suspension containing dodecylbenzene sulfonic acid to generate yttrium oxide precursor mesocrystal; and S2, treating the yttrium oxide precursor mesocrystal to obtain the yttrium oxide mesocrystal. Dodecylbenzene sulfonic acid is adopted as a surfactant to be matched with deionized water to prepare the yttrium oxide mesocrystal, the morphology of the yttrium oxide mesocrystal is snowflake-shaped or triangular prism-shaped, the granularity of the yttrium oxide mesocrystal is 0.4-2 microns, and compared with a yttrium oxide material prepared without dodecylbenzene sulfonic acid as the surfactant, the yttrium oxide mesocrystal has the pore diameter of 11.68 nm, the high specific surface area of 31.59 m < 2 > / g and multiple adsorption sites, so that the yttrium oxide mesocrystal has the advantages that the specific surface area of the yttrium oxide mesocrystal is larger than that of the yttrium oxide material prepared without dodecylbenzene sulfonic acid as the surfactant; when the relative pressure (p / p0) is 1, the adsorption performance of the yttrium oxide mesocrystal is high and reaches 59.998 cm < 3 >. G <-1 >.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of yttrium oxide preparation, and specifically relates to application of a yttrium salt suspension containing dodecylbenzenesulfonic acid, yttrium oxide mesocrystals and a preparation method and application thereof. Background Art

[0002] As a ceramic material, yttrium oxide has attracted much attention in the field of protective coatings due to its heat resistance, corrosion resistance, and high temperature stability. In the production process of integrated circuit chips, electrostatic chucks and reaction chambers are in a strong corrosive environment such as plasma during the etching, evaporation, diffusion and other processes, so strict protection capabilities are required; at the same time, the slight loss of protective coating must be controlled to prevent contamination of the wafer surface. At present, yttrium oxide is the most widely used protective coating material.

[0003] Yttria coatings for protection of electrostatic chucks and reaction chambers are prepared by plasma spraying process. The powder size and particle size distribution required by the plasma spraying process are the main factors affecting the quality of plasma sprayed coatings.

[0004] The hydrothermal synthesis method for preparing yttrium oxide powder is currently a commonly used method for preparing protective coatings for semiconductor equipment because of its high purity and small particle size.

[0005] The plasma spraying process is a complex and delicate process. First, a plasma arc is generated. The arc is ignited by a high-frequency spark, so that the working gas (such as Ar or N2) supplied to the spray gun is ionized into plasma under the action of the arc. These plasmas are compressed into a non-transfer plasma arc under the combined action of mechanical compression effect, self-magnetic compression effect and thermal compression effect; secondly, the spraying material is heated. The powder spraying material is fed into the plasma arc by the powder feed flow, and the powder material is quickly heated to a molten or semi-molten state under the high temperature of the plasma arc. Atomization granulation is one of the key steps in preparing powder materials suitable for spraying. By optimizing the atomization granulation process, high-quality spray coatings can be obtained, and the wear resistance, corrosion resistance, high-temperature oxidation resistance and other properties of the product can be improved. However, the atomization process is difficult to control, and the powder particle size distribution coefficient is high (for example, a method for preparing high-purity yttrium oxide spherical particles for thermal spraying without additives disclosed in publication number CN114195517A, in which the powder particle size is distributed in the range of 10-50 μm when the atomization process is adopted). The particle size of the powder directly affects the powder transportation and heating conditions and the density of the coating, which leads to inconsistent powder flight speeds during the plasma spraying process, affecting the plasma spray coating quality of the yttrium oxide coating.

[0006] Therefore, it is necessary to propose a yttrium oxide mesocrystal which does not require an atomization process and has a low powder force distribution coefficient, so as to reduce the inconsistency of powder flight speed during plasma spraying to solve the above problems. Summary of the invention

[0007] The invention provides an application of a yttrium salt suspension containing dodecylbenzenesulfonic acid, yttrium oxide mesocrystals and a preparation method and application thereof, aiming to realize controllable synthesis of yttrium oxide mesocrystals by adjusting the ratio of dodecylbenzenesulfonic acid as a surfactant to deionized water, wherein the number of crystal grains assembled is controllable, the distribution coefficient of the particle size is low, and no atomization granulation link is required; during the plasma spraying process, the flying speed of powder particles is less inconsistent, and the solid phase fraction of droplets is close when the powder particles absorb heat and melt and impact the surface of a substrate, which is beneficial to the plasma spraying process.

[0008] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0009] The invention discloses an application of a yttrium salt suspension containing dodecylbenzenesulfonic acid in preparing an intermediate material and a protective coating for integrated circuit equipment.

[0010] A method for preparing yttrium oxide mesocrystals comprises the following steps:

[0011] S1, a suspension of yttrium salt containing dodecylbenzenesulfonic acid is subjected to hydrothermal reaction to generate yttrium oxide precursor mesocrystal;

[0012] S2. Treating the yttrium oxide precursor mesocrystal to obtain the yttrium oxide mesocrystal.

[0013] Preferably, the yttrium salt suspension containing dodecylbenzenesulfonic acid is prepared according to the following method:

[0014] Step 1: First, dissolve the yttrium salt in dodecylbenzenesulfonic acid and then in deionized water to form a mixed solution;

[0015] Step 2: Adjust the pH of the mixed solution with alkali solution until a white colloidal suspension is formed.

[0016] Preferably, in step 1, the yttrium salt suspension containing dodecylbenzenesulfonic acid is prepared from a yttrium salt solution with dodecylbenzenesulfonic acid as solvent and yttrium salt as solute and deionized water, wherein: the concentration of the yttrium salt solution is 0.5-0.8 mol / L; and the volume ratio of dodecylbenzenesulfonic acid to deionized water is 1:0.1-3.

[0017] Preferably, in step 2, the alkali solution is sodium hydroxide or ammonia water, and the pH is adjusted to 7-11 to obtain a white colloidal suspension.

[0018] Preferably, the yttrium salt is one of yttrium nitrate, yttrium acetate and yttrium chloride.

[0019] Preferably, in step S1, the hydrothermal reaction conditions are: 80-100° C. for 9-24 h.

[0020] Preferably, in step S1, the interior of the yttrium oxide precursor mesocrystal is a nanoparticle superstructure.

[0021] Preferably, in step S2, the yttrium oxide precursor mesocrystal is prepared by drying and calcining, wherein: the drying condition is: drying at 60-80°C for 10-12h; the calcining condition is: calcining at 600-800°C for 2-4h.

[0022] Furthermore, in step S2, the yttrium oxide precursor mesocrystals are further subjected to a centrifugal washing operation before being dried.

[0023] Furthermore, the centrifugal washing condition is 5000-10000 rpm for 10 min.

[0024] A yttrium oxide mesocrystal is prepared by the above-mentioned preparation method.

[0025] Preferably, the yttrium oxide mesocrystals are in the shape of snowflakes or triangular prisms, with a particle size distribution coefficient of 0.35 to 0.64 and an average size of 0.4 to 2 μm.

[0026] The above-mentioned yttrium oxide mesocrystals are used in the preparation of intermediate materials and protective coatings for integrated circuit equipment.

[0027] The beneficial effects of the present invention are:

[0028] (1) The present invention uses dodecylbenzenesulfonic acid as a surfactant to cooperate with deionized water to prepare yttrium oxide mesocrystals, and the yttrium salt concentration is 0.5-0.8 mol / L, and the volume ratio of dodecylbenzenesulfonic acid to deionized water is 1:0.1-3; its morphology is snowflake-shaped or triangular prism-shaped, and the particle size is 0.4-2 μm. It is subjected to N2 adsorption and desorption test. The adsorption amount of different samples under the same relative pressure (p / p0) is different. The core of the test is to analyze the relationship between the adsorption amount and the relative pressure. Compared with the yttrium oxide material prepared without using dodecylbenzenesulfonic acid as a surfactant, it has a pore size of 11.68 nm and a pore size of 31.59 nm. 2 / g has a high specific surface area and multiple adsorption sites. Therefore, when the relative pressure (p / p0) is 1, the adsorption performance of yttrium oxide mesocrystal is strong, reaching 59.998cm 3 ·g -1 ;

[0029] (2) The present invention does not require an atomization process when preparing yttrium oxide mesocrystals, thus shortening the preparation process;

[0030] (3) The mesocrystals of the present invention are uniform in size, which is beneficial for plasma spraying. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 To generate the boundary map of yttrium oxide mesocrystal;

[0032] Figure 2 This is a SEM image of the yttrium oxide mesocrystal prepared in Example 1;

[0033] Figure 3 The particle size distribution diagram of the yttrium oxide mesocrystal prepared in Example 1;

[0034] Figure 4 This is a SEM image of the yttrium oxide mesocrystal prepared in Example 2;

[0035] Figure 5 This is a particle size distribution diagram of yttrium oxide mesocrystals prepared in Example 2;

[0036] Figure 6 This is a SEM image of the yttrium oxide nanosheets prepared in Example 3;

[0037] Figure 7 This is a particle size distribution diagram of yttrium oxide mesocrystals prepared in Example 3;

[0038] Figure 8 This is a SEM image of the yttrium oxide mesocrystal prepared in Example 4;

[0039] Fig. 9 This is a particle size distribution diagram of yttrium oxide mesocrystals prepared in Example 4;

[0040] Fig.10 BET diagram of yttrium oxide mesocrystal prepared in Example 4;

[0041] Fig.11 This is a SEM image of the rod-shaped yttrium oxide prepared in Comparative Example 1;

[0042] Fig.12 This is the BET diagram of the rod-shaped yttrium oxide prepared in Comparative Example 1;

[0043] Fig.13 The size of the prepared yttrium oxide mesocrystals changes with the proportion of surfactants;

[0044] Fig.14 This is a comparison chart of the coating bonding strength between Comparative Example 1 and Example 4. DETAILED DESCRIPTION

[0045] In order to make the technical means, creative features, objectives and effects of the present invention easier to understand, the present invention is further described below with reference to specific illustrations.

[0046] The present invention also needs to make the following glossary:

[0047] noun meaning Matrix Corundum Alumina Reaction system Dodecylbenzenesulfonic acid-deionized water-ammonia system Solute Yttrium salt

[0048] Example 1

[0049] The preparation method of yttrium oxide mesocrystal comprises the following steps:

[0050] Weigh 9.25g of yttrium acetate, dissolve it in dodecylbenzenesulfonic acid first, prepare a yttrium acetate solution with a concentration of 0.6mol / L, and then dissolve it in deionized water. Add ammonia water while stirring to adjust the pH of the solution to 10, wherein the volume of dodecylbenzenesulfonic acid is 18mL, the volume of deionized water is 29mL, and the volume of ammonia water is 13mL, and a white colloidal suspension is obtained; the white colloidal suspension is moved to a hydrothermal reactor and filled with N2 to exhaust the oxygen in the air (the reason is: dodecylbenzenesulfonic acid and oxygen may undergo an oxidation reaction. This reaction will cause the alkyl chain in the molecular structure to be oxidized, which may produce into oxygen-containing compounds such as alcohols, acids, and ketones. N2 is flushed in to prevent over-oxidation or other undesirable side reactions); hydrothermal treatment is performed at 90°C for 24 hours; the liquid after the hydrothermal reaction is cooled to room temperature and centrifuged to separate the yttrium oxide precursor mesocrystals, and the obtained yttrium oxide precursor mesocrystals are centrifugally washed at 9000rpm for 10 minutes, and washed at least 2 to 3 times to fully remove residual impurities; the precursor is vacuum dried at 80°C for 12 hours, and after drying, calcined at 600°C for 4 hours to obtain yttrium oxide mesocrystals. Scanning under a scanning electron microscope shows that the microscopic morphology of the mesocrystal is columnar, such as Figure 2 As shown, the particle size is about 0.92 to 2 μm.

[0051] Example 2

[0052] This embodiment is basically the same as embodiment 1, except that, in this embodiment, the concentration of yttrium acetate solution is 0.5 mol / L, the volume of dodecylbenzenesulfonic acid is 24 mL, deionized water is 18 mL, ammonia water is 18 mL, and calcination is performed at 800° C. for 2 h. The obtained yttrium oxide mesocrystal is observed under a scanning electron microscope, and the microscopic morphology of the mesocrystal is as follows: Figure 4 As shown, the length is 0.89-1.83 μm, and the side length of the cross-sectional triangle is 0.67-0.89 μm;

[0053] Example 3

[0054] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, the mass of yttrium acetate is 12.33 g, the concentration of yttrium acetate solution is 0.8 mol / L, deionized water is 16 mL, and ammonia water is 20 mL; the precursor is vacuum dried at 60° C. for 12 h, and calcined at 800° C. for 2 h to obtain yttrium oxide mesocrystals. Scanning under a scanning electron microscope shows that the microscopic morphology of the mesocrystals is 0.35 to 0.56 μm long, and the side length of the cross-sectional triangle is 0.55 to 0.75 μm.

[0055] Example 4

[0056] This embodiment is basically the same as embodiment 1, except that, in this embodiment, the volume of dodecylbenzenesulfonic acid is 36 mL, deionized water is 7 mL, and ammonia water is 17 mL; yttrium oxide mesocrystals are obtained, and the microscopic morphology of the mesocrystals is scanned under a scanning electron microscope, showing a snowflake shape, as shown in FIG. Figure 8 As shown, the particle size is about 0.44 to 0.63 μm.

[0057] In order to explore its particle size distribution, the particle size distribution diagram under Examples 1-4 is as follows Figure 3 , 5 , 7, 9, for this reason, according to the particle size distribution coefficient formula PDI = (D 90 -D 10 ) / D 50 The PDI values ​​of Examples 1-4 are summarized, where D 10 Indicates the diameter of 10% of the particles in the sample, D 50 Indicates the diameter of particles with a diameter of 50% in the sample, D 90 Indicates the diameter of 90% of the particles in the sample. See Table 1 for details.

[0058] Table 1:

[0059] <![CDATA[D 90 (μm)]]> <![CDATA[D 50 (μm)]]> <![CDATA[D 10 (μm)]]> PDI Example 1 1.8 1.38 0.9 0.65 Example 2 1.72 1.37 0.9 0.59 Example 3 0.72 0.54 0.37 0.64 Example 4 0.6 0.51 0.42 0.35

[0060] As can be seen from Table 1, the powder particle size of yttrium oxide mesocrystals is between 0.37-1.8 μm, and its PDI is between 0.35-0.65. In particular, in Example 4, the powder particle size is between 0.42-0.6 μm, which is much smaller than the powder particle size of 10-50 μm disclosed in the patent with publication number CN114195517A, which can directly affect the powder transportation and heating conditions and the density of the coating, resulting in less inconsistent powder flight speed during plasma spraying, thereby improving the plasma spraying coating quality of the yttrium oxide coating.

[0061] For the snowflake-shaped yttrium oxide mesocrystals in Example 4, the present invention uses the N2 adsorption-desorption curve recorded in "Quantitative Analysis of Nitrogen Adsorption Hysteresis Loops and Its Indicative Significance in Pore Structure Characterization - Taking the 7th Section of the Upper Triassic Yanchang Formation in the Ordos Basin as an Example" published by Song Zezhang et al. in April 2023 to study its specific surface area and pore structure characteristics. The N2 adsorption stripping curvature and pore size distribution curve are shown in Fig.10 As shown. Fig.10 It can be seen that the specific surface area of ​​the snowflake-like yttrium oxide mesocrystal is 31.59 m 2 / g, the larger the specific surface area, the stronger the adsorption capacity.

[0062] Summarizing Examples 1-4, it can be found that as the proportion of dodecylbenzenesulfonic acid as a surfactant increases, the size of the mesogens gradually decreases, such as Fig.13As shown, the reason is that the addition of surfactants increases the viscosity of the reaction system. According to the Einstein-Stokes theorem, the viscosity is inversely proportional to the diffusion coefficient of the solute, and the solute must migrate from the solution to the surface of the crystal nucleus, thereby determining the growth rate of the crystal. Therefore, the higher the surfactant / H2O ratio, the smaller the final product size.

[0063] Summarizing the formation of mesocrystal morphology, it is found that dodecylbenzenesulfonic acid as a surfactant and the yttrium salt solution formed after the yttrium salt is dissolved in the surfactant and its ratio, yttrium salt concentration play a key role in the formation of mesocrystals. Both can generate yttrium oxide mesocrystals within a certain boundary range, such as Figure 1 As shown, the concentration of yttrium salt is 0.5-0.8 mol / L, and the volume ratio of dodecylbenzenesulfonic acid to deionized water is 1:0.1-3 to generate mesocrystals;

[0064] When the concentration of yttrium salt is less than 0.5 mol / L and the volume ratio of dodecylbenzenesulfonic acid to deionized water is less than 30%, the mesomorphic morphology cannot be obtained.

[0065] When the concentration of yttrium salt is greater than 0.8 mol / L and the volume ratio of dodecylbenzenesulfonic acid to deionized water is greater than 60%, the experiment cannot be performed.

[0066] Comparative Example 1

[0067] This embodiment is basically the same as embodiment 1, except that in this embodiment, the surfactant used is polyvinyl pyrrolidone, and its volume is 36 mL, deionized water 4 mL, ammonia water 20 mL; rod-shaped yttrium oxide is obtained, such as Fig.10 As shown, the particle size is about 1.9 to 4.5 μm.

[0068] For rod-shaped yttrium oxide, the specific surface area and pore structure characteristics were studied by N2 adsorption-desorption isotherm method. N2 adsorption stripping curvature and pore size distribution curve, such as Fig.12 As shown in the figure, the specific surface area of ​​the powder sample is 17.074m 2 / g.

[0069] By comparing Example 4 and Comparative Example 1, it can be obtained that: when other conditions remain unchanged, only changing the type of surfactant has a great influence on the morphology and performance of the product. The specific surface area and pore structure characteristics of different product morphologies corresponding to dodecylbenzenesulfonic acid and polyvinylpyrrolidone are discussed. The specific surface area corresponding to the mesomorphic morphology is much larger than that of the rod-like morphology, and the specific surface area determines the adsorption capacity.

[0070] The assembly quantity of the mesogenic crystal particles prepared by the invention is controllable, the distribution coefficient of the particle size is low, and no atomization granulation step is required.

[0071] The tensile strength test can accurately reflect the bonding strength between the coating and the substrate. The specific method is: install the sample on a tensile testing machine, and gradually apply tensile force on the testing machine until the coating falls off the substrate.

[0072] Record the maximum tensile force (F) when the coating falls off and combine it with the strength calculation formula: RH = F / S, where F is the maximum tensile force when the coating falls off (unit: N), and S is the cross-sectional area of ​​the interface between the coating and the substrate (unit: mm 2 ).

[0073] Fig.14 The figure shows the description of the coating bonding strength obtained by the atomization granulation step and the coating bonding strength without the atomization granulation step in the present invention. It can be found that the mesocrystals prepared by the present invention have stronger bonding ability during the spraying process without the atomization granulation step (the average bonding strength of Example 4 can reach 20MPa, and the average bonding strength of Comparative Example 1 is 12MPa), so the mesocrystal morphology obtained by the present invention can be better applied to plasma spraying.

[0074] After purity testing, the purity of yttrium oxide mesocrystals obtained by the present invention according to the yttrium oxide purity calculation method in XB / T511-2020 can reach 99%.

[0075] The above shows and describes the basic principles and main features of the present invention and the advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. Application of yttrium salt suspension containing dodecylbenzenesulfonic acid in the preparation of coating intermediate materials and protective coatings.

2. A method for preparing yttrium oxide mesocrystals, characterized in that: The following steps are involved: S1, a suspension of yttrium salt containing dodecylbenzenesulfonic acid is subjected to hydrothermal reaction to generate yttrium oxide precursor mesocrystal; S2. Treating the yttrium oxide precursor mesocrystal to obtain the yttrium oxide mesocrystal.

3. The method for preparing yttrium oxide mesocrystal according to claim 1, characterized in that: In step S1, the yttrium salt suspension containing dodecylbenzenesulfonic acid is prepared from a yttrium salt solution with dodecylbenzenesulfonic acid as solvent and yttrium salt as solute and deionized water, wherein: the concentration of the yttrium salt solution is 0.5-0.8 mol / L; the volume ratio of dodecylbenzenesulfonic acid to deionized water is 1:0.1-3.

4. A method for preparing yttrium oxide mesocrystal according to claim 2, characterized in that: The yttrium salt is one of yttrium nitrate, yttrium acetate and yttrium chloride.

5. A method for preparing yttrium oxide mesocrystal according to claim 2, characterized in that: In step S1, the hydrothermal reaction conditions are: 80-100° C. for 9-24 hours.

6. The method for preparing yttrium oxide mesocrystal according to claim 2, characterized in that: In step S1, the interior of the yttrium oxide precursor mesocrystal is a nanoparticle superstructure.

7. The method for preparing yttrium oxide mesocrystal according to claim 6, characterized in that: In step S2, the yttrium oxide precursor mesocrystal is obtained by drying and calcining, wherein: the drying condition is: drying at 60-80°C for 10-12h; the calcining condition is: calcining at 600-800°C for 2-4h.

8. A yttrium oxide mesocrystal, characterized in that: Prepared by the preparation method according to any one of claims 2 to 7.

9. The yttrium oxide mesocrystal according to claim 8, characterized in that: The yttrium oxide mesocrystal has a snowflake shape or a triangular prism shape, a particle size distribution coefficient of 0.35-0.64, and an average size of 0.4-2 μm.

10. Use of the yttrium oxide mesocrystal according to any one of claims 8 or 9 in the preparation of coating intermediate materials and protective coatings.